Current collector for lead-acid battery, positive electrode plate for lead-acid battery, and lead-acid battery

The current collector for lead-acid batteries, with a controlled mass and contour ratio, addresses deformation and detachment issues by promoting uniform corrosion and improved binding, ensuring superior life performance.

JP7601092B2Active Publication Date: 2024-12-17GS YUASA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022515212
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-14
Filing Date
2021-01-29
Publication Date
2024-12-17
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

Existing lead-acid battery current collectors experience deformation and electrode material detachment during high-temperature overcharge tests due to uneven corrosion and stress, leading to reduced life performance.

Method used

A current collector design with a specific mass ratio (W1/W2 of 0.2 to 0.42) and contour ratio (R1 of 50% or more) is implemented, featuring a striped pattern of metallic fibrous tissue, which minimizes uneven corrosion and stress, ensuring uniform corrosion progression and enhanced binding force with the electrode material.

Benefits of technology

The design significantly reduces deformation and elongation of the current collector, preventing electrode material detachment and maintaining excellent life performance even under high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601092000005
    Figure 0007601092000005
  • Figure 0007601092000006
    Figure 0007601092000006
  • Figure 0007601092000007
    Figure 0007601092000007
Patent Text Reader

Abstract

A current collector for a lead storage battery, according to the present invention, comprises a frame skeleton and an inner skeleton inside the frame. The frame skeleton is equipped with an ear, an upper element connecting to the ear, a lower element facing the upper element, and a pair of side elements connecting the upper element and the lower element. The inner skeleton is equipped with a vertical skeleton extending in a first direction from the upper element toward the lower element, and a horizontal skeleton extending in a second direction from one of the side elements toward the other side element. A striped pattern of a metal fibrous structure is seen in a cross section perpendicular to the first direction of the vertical skeleton, and an outer peripheral region of the cross section is formed of a first portion in which the fibrous structure extends along the contour of the cross section and a second portion other than the first portion. The ratio of the length of the contour corresponding to the first portion to the entire length of the contour of the cross section is 50% or more, and the ratio W1 / W2 of the mass W1 of the frame skeleton to the mass W2 of the inner skeleton satisfies the equation 0.2 ≤ W1 / W2 ≤ 0.42.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a current collector for a lead-acid battery, a positive electrode plate for a lead-acid battery, and a lead-acid battery. [Background technology]

[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries are equipped with an electrode plate group in which positive and negative electrode plates are alternately stacked with separators between them. The electrode plate is composed of a current collector and an electrode material held by the current collector.

[0003] Patent Document 1 proposes a lead grid plate for a lead storage battery, which is obtained by pressing a rolled plate of a lead alloy, and in which the thickness of the internal vertical and horizontal bars is thinner than the thickness of the outer frame, and the thickness of the outer frame is in the range of 0.8 to 1.5 mm, and the thickness of the internal bars is in the range of 0.6 to 0.8 mm. Patent Document 1 also proposes a lead grid plate for a lead storage battery, which is obtained by pressing a rolled plate of a lead alloy having a thickness of 1.2 to 1.5 mm, and in which the thickness of the internal vertical and horizontal bars is set in the range of 0.6 to 0.8 mm by deforming the inner frame in the thickness direction.

[0004] Patent document 2 proposes a positive-electrode grid substrate that comprises a frame, tabs arranged on the outside of the frame, and inner frames arranged on the inside of the frame to form a grid, in which the added mass of the frame and tabs (frame + tabs) is lighter than the mass of the inner frames.

[0005] Patent Document 3 proposes a grid body for a lead-acid battery having a frame and an inner frame consisting of multiple horizontal bars and multiple vertical bars, in which the upper ends of the multiple vertical bars are each connected to an upper horizontal bar of the frame and the multiple vertical bars extend toward the lower horizontal bar of the frame without crossing each other, and the mass of the upper horizontal bar of the frame is set to 11% to 14% of the mass of the entire grid body, and the mass is distributed so that the combined mass of the upper horizontal bar and the multiple vertical bars is 60% to 70% of the mass of the entire grid body. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 51-60936 [Patent Document 2] JP 2012-174561 A [Patent Document 3] Japanese Patent Application Publication No. 5-54893 Summary of the Invention [Problem to be solved by the invention]

[0007] In Patent Documents 1 and 2, it is believed that the retention of the electrode material can be improved to some extent by adjusting the balance of the thickness or mass of the lattice-shaped current collector. In Patent Document 3, it is believed that the decrease in current collection ability or the deterioration of the electrode material can be suppressed to some extent by controlling the voltage characteristics of the lattice-shaped current collector. However, when a high-temperature overcharge test is performed, the lattice-shaped current collector is significantly stretched or curved, and the electrode material may fall off, resulting in a decrease in life performance. [Means for solving the problem]

[0008] One aspect of the present invention is a current collector for a lead-acid battery, A frame and an inner frame on the inside of the frame, The frame includes an ear, an upper element continuous with the ear, a lower element facing the upper element, and a pair of side elements connecting the upper element and the lower element, The inner bone includes a vertical bone extending in a first direction from the upper element to the lower element, and a horizontal bone extending in a second direction from one of the side elements to the other of the side elements, A striped pattern of a fibrous metal structure is seen in a cross section of the longitudinal bone perpendicular to the first direction; The outer peripheral region of the cross section is composed of a first portion in which the fibrous structure extends along the contour of the cross section, and a second portion other than the first portion, A ratio R1 of the length of the contour corresponding to the first portion to the total length of the contour of the cross section is 50% or more; The ratio of the mass W1 of the frame to the mass W2 of the inner frame: W1 / W2 is 0.2≦W1 / W2≦0.42 The present invention relates to a current collector for a lead-acid battery that satisfies the above requirements. [Brief description of the drawings]

[0009] [Figure 1A] 1 is a plan view showing the appearance of a current collector for a lead-acid battery according to one embodiment of the present invention. FIG. [Figure 1B] FIG. 4 is a plan view showing the appearance of a current collector for a lead-acid battery according to another embodiment of the present invention. [Figure 2A] This is a cross-sectional photograph perpendicular to the first direction of the longitudinal bone. [Figure 2B] 1 is a conceptual diagram of cross section C. [Diagram 3] This is a cross-sectional photograph of an inner bone showing the cross section of fibrous tissue. [Figure 4] FIG. 1 is a conceptual cross-sectional view showing the progression of corrosion of the inner bone. [Diagram 5] 1 is a perspective view showing the appearance of a lead-acid battery according to one embodiment of the present invention; [Figure 6] 1 is a graph showing the relationship between the current collector ratio W1 / W2 and the initial capacity ratio after a repeated 5-h charge-discharge test after high-temperature overcharge. [Figure 7] 1 is a graph showing the relationship between the current collector ratio R1 and the corrosion rate and the deformation amount (width elongation and height elongation). [Figure 8] 1 is a graph showing the relationship between the current collector ratio R1 and the initial capacity ratio after a repeated 5-hR charge-discharge test. [Figure 9] 1 is a graph showing the relationship between WLH / WLW and lateral elongation of a current collector. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A current collector for a lead-acid battery according to one aspect of the present invention has a frame and an inner frame inside the frame. The frame has a lug, an upper element continuous with the lug, a lower element facing the upper element, and a pair of side elements connecting the upper element and the lower element. The inner frame has a vertical bone extending in a first direction from the upper element to the lower element, and a horizontal bone extending in a second direction from one side element to the other side element. A striped pattern of a fibrous texture of metal can be seen in a cross section perpendicular to the first direction of the vertical bone. The outer peripheral region of the cross section is composed of a first portion where the fibrous texture extends along the contour of the cross section, and a second portion other than the first portion. The ratio R1 of the length of the contour corresponding to the first portion to the total length of the contour of the cross section is 50% or more. The ratio W1 / W2 of the mass W1 of the frame to the mass W2 of the inner frame satisfies 0.2≦W1 / W2≦0.42.

[0011] The current collector is also called a lattice. However, the skeleton of the current collector or lattice is not limited to a lattice or mesh shape.

[0012] The frame (more specifically, the portion of the frame excluding the ears) is generally generally quadrangular, and may be rectangular. The quadrangular shape may be a quadrangular shape (e.g., a trapezoid) in which at least one of the angles formed by the upper element and each of the pair of side elements, and the angle formed by the lower element and each of the pair of side elements (a total of four angles) is not 90°. At least one of the four corners of the quadrangular shape may be chamfered. The chamfering may be C-chamfering or R-chamfering. R-chamfering, which rounds the corners, is usually preferred.

[0013] When the frame is rectangular, the first direction is a direction parallel to the side elements, and the second direction is a direction parallel to the upper and lower elements. When the frame is quadrilateral other than a rectangle and the battery is a flooded lead-acid battery, the first direction corresponds to the vertical direction and the second direction corresponds to the horizontal direction in normal use of the lead-acid battery. When the frame is quadrilateral other than a rectangle and the battery is a valve regulated lead-acid battery, the first direction corresponds to the vertical direction (or horizontal direction) and the second direction corresponds to the horizontal direction (or vertical direction) in normal use of the lead-acid battery.

[0014] The longitudinal bones may extend parallel to the side elements or diagonally to the side elements. The longitudinal bones may be straight, curved, or slightly bent. In other words, the longitudinal bones may extend such that the vector in the first direction is greater than the vector in the second direction.

[0015] The cross bone may extend parallel to the upper or lower element, or may extend diagonally to the upper or lower element. The cross bone may be straight, curved, or slightly bent. That is, the cross bone may extend such that the vector in the second direction is greater than the vector in the first direction.

[0016] A striped pattern of the fibrous structure of the metal is observed in a cross section perpendicular to the first direction of the longitudinal bone, i.e., in a cross section parallel to the upper element and parallel to the thickness direction (hereinafter also referred to as cross section C). The peripheral region of cross section C is composed of a first part in which the fibrous structure (direction of the stripes) extends along the contour of cross section C, and a second part other than the first part. The contour of cross section C means a line corresponding to the outer surface of the longitudinal bone. The peripheral region of cross section C is a peripheral region along the contour of cross section C, and has a depth of at least 55 μm or more, preferably 100 μm or more, from the line corresponding to the outer surface in cross section C. In the second part of cross section C, a striped pattern may not be observed, and a striped pattern extending in the depth direction of the peripheral region may be observed.

[0017] In the lead-acid battery according to the above aspect of the present invention, the ratio R1 is set to 50% or more, and the ratio W1 / W2 is controlled to be in the range of 0.2 to 0.42. This makes it possible to ensure excellent life performance after high-temperature overcharge. The reason why such an effect is obtained will be explained in more detail below. Note that the ratio R1 being 50% or more means that the ratio R2 is 50% or less.

[0018] In this way, when the ratio R1 or the ratio R2 is controlled, the cross section perpendicular to the fiber length of the fibrous structure is less likely to be exposed on the outer surface of the peripheral region of the cross section C. The cross section perpendicular to the fiber length of the fibrous structure has many grain boundaries. The corrosion progresses differently between the first portion and the second portion.

[0019] In general, corrosion of the current collector proceeds preferentially in a cross section perpendicular to the fiber length of the fibrous structure exposed on the outer surface. In the outer surface of the first part of the outer peripheral region, the fibrous metal structure extends in the surface direction of the inner bone. That is, the grain boundaries extend longer in the surface direction of the inner bone than in the depth direction of the inner bone. Therefore, the corrosion layer formed in the first part of the outer peripheral region is formed along the surface direction of the inner bone and is unlikely to be formed deep inside the inner bone. The corrosion layer formed along the outer surface of the first part of the outer peripheral region has low bonding strength with the current collector (inner bone). Therefore, when gas is generated at the interface between the current collector (outer surface of the first part of the outer peripheral region) and the corrosion layer, the corrosion layer peels off relatively easily from the current collector. In this way, in the first part, the stress accompanying the peeling of the corrosion layer is unlikely to be applied to the current collector, so that the elongation and deformation of the current collector are reduced.

[0020] On the other hand, on the outer surface of the second part of the outer peripheral region, the fibrous metal structure extends in the depth direction of the inner bone. That is, the grain boundaries extend longer in the depth direction of the inner bone than in the surface direction of the inner bone. Therefore, in the second part, the corrosion of the vertical bone tends to progress deep in a wedge shape, and the elongation of the current collector due to deep corrosion tends to be large. Therefore, the corrosion layer formed along the outer surface of the second part of the outer peripheral region has a high bonding strength with the current collector (inner bone). In the second part, even if gas is generated at the interface between the current collector and the corrosion layer, the corrosion layer is unlikely to peel off from the current collector. Therefore, the stress associated with the gas generation is applied to the inner bone, and the current collector is likely to elongate or deform. In particular, when an overcharge test is performed at a high temperature (for example, a temperature of 60°C or higher), the corrosion of the current collector is more likely to progress, and gas generation is prominent, so that the effect of the stress received by the corrosion layer on the second part is likely to become apparent. Therefore, even if the amount of corrosion is the same, the larger the ratio R1, the more the elongation and deformation of the current collector is suppressed, and the more the electrode material is suppressed from falling off.

[0021] In a cross section perpendicular to the second direction of the cross bone of the current collector, i.e., a cross section parallel to the side element and parallel to the thickness direction (hereinafter also referred to as cross section G), the stripes of the metal fibrous structure are hardly seen, and a cross section perpendicular to the fiber length of the fibrous structure is generally seen. The peripheral region of cross section G usually corresponds to the second part in cross section C almost entirely. In other words, the peripheral region of cross section G is composed of a fibrous structure extending in the second direction almost entirely. Therefore, in the peripheral region of cross section G, elongation or deformation of the current collector is suppressed even if the amount of corrosion is the same.

[0022] By controlling the ratio W1 / W2, it becomes easier to ensure the binding force of the electrode material, and deformation of the inner bone can be suppressed to a certain extent. However, due to the difference in the progress of corrosion between the first part and the second part as described above, even if the amount of corrosion is the same, the degree of deformation of the current collector is significantly different. This causes the current collector to elongate in one direction, or the stress applied to the current collector varies, causing distortion and curvature. In particular, deformation (elongation, curvature, etc.) of the current collector becomes significant in the high-temperature overcharge test. According to the above aspect of the present invention, the ratio W1 / W2 is controlled to a range of 0.2 to 0.42, and the proportion R1 is set to 50% or more. Therefore, even if high-temperature overcharge is performed, the deformation itself due to the stress of the corrosion layer is reduced. In addition, the degree of progress of corrosion can be made more uniform throughout the entire inner bone, the uneven distribution of the corrosion layer is suppressed, and the elongation or deformation of the current collector is suppressed. Furthermore, since the discharge reaction can be made to proceed more uniformly from the beginning, the decrease in adhesion between the current collector and the electrode material is suppressed even if charging and discharging are repeated. As a result, the electrode material is prevented from falling off, and excellent life performance after high-temperature overcharge can be ensured.

[0023] The ratio R1 of the first portion may be 50% or more. When the ratio R1 is 50% or more, the effect of suppressing the height elongation of the current collector is enhanced. From the viewpoint of enhancing the effect of suppressing the width elongation of the current collector, the ratio R1 is preferably 60% or more or 70% or more, and may be 75% or more or 80% or more. In addition, the ratio R1 is preferably less than 100%, and more preferably 95% or less or 90% or less. When the ratio R1 is 100%, the degree of corrosion progresses uniformly around the entire circumference of the inner bone, but when the ratio R1 exceeds 95%, for example, the initial capacity ratio after charging and discharging the capacity at a 5-hour rate current tends to decrease significantly. For example, the initial capacity ratio of the capacity obtained by discharging around 5 cycles may decrease to less than 70%. On the other hand, when the ratio R1 is 95% or less, the initial capacity ratio of the capacity around 5 cycles can be 75% or more or 80% or more.

[0024] When charging and discharging at a 5-hour rate current is repeated, the electrode material expands and contracts repeatedly, and the interface between the current collector and the electrode material becomes more likely to physically peel off. This is thought to be the cause of the decrease in the initial capacity ratio. It is thought that the first portion is more likely to form a shallow layer of corrosion, while the second portion is more likely to form a deep wedge-shaped corrosion layer. Therefore, the binding strength between the current collector and the electrode material is higher in the second portion than in the first portion. From the viewpoint of improving the binding strength between the current collector and the electrode material, it is preferable to set the proportion R2 of the second portion to 5% or more, and more preferably 10% or more.

[0025] The ratios R1 and R2 can be intentionally controlled. Even if the ratio R2 of the vertical bone is originally large, it is possible to deform the vertical bone so as to crush the second portion. For example, when deforming the vertical bone by press working, the ratio R1 can be arbitrarily controlled by the press speed, press pressure, mold shape, etc. In other words, deforming the vertical bone by press working is not a sufficient condition for increasing the ratio R1, and it is necessary to appropriately control the press working conditions.

[0026] The shape of the cross section C of the vertical bone is not particularly limited, but is preferably an octagon. When the cross section C is octagonal, the interior angle of the apex is not too small, and the effect of suppressing corrosion near the apex is easily improved. To form a vertical bone with an octagonal cross section C, for example, a vertical bone with a rectangular cross section C may be deformed. The method of deforming the vertical bone is not particularly limited, but for example, the inner bone of the current collector may be pressed. At that time, the pressing conditions of the inner bone may be appropriately selected so that the ratio R1 of the first portion is within a predetermined range. By making the shape of the cross section C octagonal, it is easy to control the ratio R1 to 50% or more. The octagon does not have to be a strict octagon in the mathematical sense, and the apex may be somewhat rounded or each side may be somewhat curved.

[0027] The above-mentioned aspect of the present invention is useful when a punched current collector is used as the current collector. As the punched current collector, a punched current collector of a drawn sheet of lead or a lead alloy is preferable. The drawn sheet is easy to generate a striped pattern of a fibrous texture of the metal, so that it is easy to adjust the ratio of the second part.

[0028] In the first portion, the fibrous structure (direction of stripes) extends along the contour of the outer peripheral region of the cross section C, which refers to the following state. First, the inside of the frame of the current collector is cut so as to be divided into three equal parts: an upper region on the upper element side of the frame, a lower region on the lower element side of the frame, and a middle region between the upper and lower regions. At this time, four rows of cross sections C perpendicular to the first direction (parallel to the upper element and parallel to the thickness direction) are formed in the multiple vertical bones. That is, one row of cross sections C is formed in each of the upper and lower regions, and two rows of cross sections C are formed in the middle region. When the dividing line for dividing into three equal parts corresponds to the intersection (node) of the vertical bones and the horizontal bones, the dividing line may be shifted slightly overall or partially to divide the current collector into three parts so that the cross section C is formed in the vertical bone part between the intersections as much as possible. When dividing the inside of the frame of the current collector into three parts, the dimensions of the ears or feet are not taken into consideration.

[0029] Next, a plurality of cross sections C to be observed (60% or more of the cross sections C included in the two rows) are selected from any two rows out of the four rows. Of the peripheral region of the selected cross section C, the portion in which the stripes of the fibrous tissue have an angle of less than 45° with the contour of the cross section C based on the horizontal plane in the first direction from the side element is the first portion. The portion other than the first portion is the second portion. Specifically, at any point P on the contour of each cross section C, a tangent S1 to the point P is drawn, and further, a perpendicular line L to the tangent S1 is drawn so as to pass through the point P. Next, a tangent S2 of the stripe that exists at a depth of 55 μm from the point P on the perpendicular line L and intersects with the perpendicular line L is drawn at the intersection. If the angle θ between the tangent S2 and the tangent S1 is less than 45°, the point P constitutes the contour corresponding to the first portion. If the angle θ is 45° or more, the point P constitutes the contour corresponding to the second portion. Even when it is not possible to determine whether point P forms a contour corresponding to the first portion because fibrous tissue cannot be observed, point P forms the contour of the second portion. For all selected cross sections C, the ratio of the length of the contour corresponding to the first portion to the total length of the contour of cross section C is found and averaged to calculate ratio R1. The ratio R2 (%) of the second portion is calculated by subtracting the average value of the ratios R1 (%) of the first portion from 100. If the cut portion is an intersection (node) between the vertical bone and the horizontal bone, the average can be calculated excluding that cross section, and the cut position of the vertical bone may be shifted so as to avoid the node.

[0030] When forming cross section C, the prepared current collector is embedded in a thermosetting resin so that it is entirely covered, the resin is cured, and then the current collector is cut together with the cured resin. The state of the metal structure of cross section C is observed by photographing the cross section of the current collector under a microscope after etching the cross section. A current collector taken by dismantling a fully charged lead-acid battery is used as the current collector.

[0031] The current collector can be removed from the battery by the following procedure. First, a fully charged lead-acid battery is disassembled, and the removed electrode plate (such as the positive electrode plate) is washed with water to remove the electrolyte containing sulfuric acid, and then dried. After that, most of the electrode material is scraped off from the electrode plate. The remaining positive electrode material adhering to the surface of the current collector is removed using an aqueous solution containing mannitol. The current collector from which the electrode material has been removed is washed with water and dried to prepare a current collector for measurement.

[0032] In this specification, the fully charged state of a flooded lead-acid battery is defined by the definition of JIS D 5301:2006. More specifically, the fully charged state is defined as a state in which a lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) 0.2 times the value listed as the rated capacity (Ah) until the terminal voltage during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which a lead-acid battery is charged at a constant current and constant voltage of 2.23 V / cell in an air tank at 25°C ± 2°C with a current (A) 0.2 times the value listed as the rated capacity (Ah), and charging is terminated when the charging current (A) during constant voltage charging becomes 0.005 times the value listed as the rated capacity (Ah). The value listed as the rated capacity is expressed in Ah. The unit of current set based on the value stated as the rated capacity is A.

[0033] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically formed and is fully charged. A lead-acid battery may be fully charged immediately after chemical formation, or after a period of time has passed since chemical formation (for example, a lead-acid battery that has been in use (preferably in the early stages of use) after chemical formation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.

[0034] The mass W1 of the frame and the mass W2 of the inner frame are measured for a current collector taken out of a fully charged lead-acid battery. Prior to measuring W1 and W2, the current collector is separated into the frame and the inner frame by cutting the boundary between the frame and the inner frame.

[0035] In cross section C, the thickness of the first portion (in other words, the thickness of the fibrous tissue) may be 55 μm or more. In addition, even if the outer peripheral region appears to be the first portion at first glance, if the thickness of the region where the striped pattern of the fibrous tissue is observed is less than 55 μm, it is considered to be the second portion rather than the first portion. The first portion having a thickness of 55 μm or more has a sufficient effect of suppressing the penetration of corrosion into the inner bone. In this case, the penetration of corrosion into the inside is likely to be highly uniform throughout the entire inner bone. Therefore, the elongation and distortion of the current collector are significantly suppressed, and the drop-off of the electrode material is also significantly suppressed. From the viewpoint of further suppressing the penetration of corrosion into the inside of the vertical bone, the thickness of the first portion is preferably 100 μm or more.

[0036] The thickness of the first portion at cross section C may be measured as follows. First, a tangent line S1 is drawn at an arbitrary point P1 on the contour of the first portion, and a perpendicular line L to the tangent line S1 is drawn passing through point P1. Next, at a point Px moving from point P1 to a depth of X μm on the perpendicular line L, a stripe tangent line S2 is continuously drawn that intersects with the perpendicular line L. At this time, if the angle between the tangent line S1 and the tangent line S2 is continuously 45° or less, it can be said that the thickness of the first portion directly below point P1 is X μm or more.

[0037] The thickness of the inner bone may be, for example, 0.7 mm to 3 mm. The width of the inner bone may be, for example, 0.7 mm to 3 mm.

[0038] When the current collector is a punched current collector of an elongated sheet of lead or lead alloy, the total length WLW of the horizontal ribs and the total length WLH of the vertical ribs may satisfy WLH / WLW≧0.8 or WLH / WLW≧1.3. In this case, since the corrosion of the current collector tends to progress toward the inside, the suppression of the elongation and distortion of the current collector is more remarkable by controlling the ratio R2 to less than 50%. Here, the inside length of each inner rib means the length of the lattice square in the inside dimension, that is, the length of the side of the rectangular space that defines the square (the length of the bar). Note that the direction of the length WLW (the direction in which the horizontal ribs extend) usually corresponds to the stretching direction (MD direction) of the stretched sheet.

[0039] When the current collector is a punched current collector made of an expanded sheet of lead or a lead alloy, the total length WLW of the inside dimensions of the horizontal bones and the total length WLH of the vertical bones may satisfy WLH / WLW≦1.96.

[0040] The above-mentioned effect is remarkable when the above-mentioned current collector is applied to a positive electrode plate, but this is not limited to this case and it may be applied to a negative electrode plate. From the viewpoint of suppressing the elongation due to corrosion of the current collector, it is preferable to use the above-mentioned current collector at least for the positive electrode plate. In addition, when a lead-acid battery has a plurality of positive electrode plates, the above-mentioned current collector may be used for some of the positive electrode plates, or the above-mentioned current collector may be used for all of the positive electrode plates. Similarly, when a lead-acid battery has a plurality of negative electrode plates, the above-mentioned current collector may be used for at least some of the negative electrode plates, or the above-mentioned current collector may be used for all of the negative electrode plates.

[0041] The current collector can be manufactured by a manufacturing method including pressing an intermediate bone, which is a precursor of an inner bone. Such a manufacturing method includes, for example, (i) a step of preparing a rolled plate, (ii) a step of forming an intermediate lattice having a plurality of intermediate bones formed in a lattice shape by punching the rolled plate, (iii) a step of pressing the intermediate lattice in the thickness direction of the intermediate lattice to form at least a part of the inner bone, and (iv) a step of adjusting the mass distribution state so that W1 / W2 in the current collector is 0.2≦W1 / W2≦0.42. Here, the press processing includes a step of deforming at least a part of the plurality of intermediate bones so that at least one end in the bone width direction is thinner than the center in the bone width direction intersecting the extension direction of the intermediate bone (for example, perpendicular to the extension direction) and the ratio R1 is within the above range.

[0042] In step (iv), for example, the mass distribution is adjusted in at least one of the rolled plate and the intermediate grid so that W1 / W2 in the current collector falls within the above range. In the rolled plate, for example, the mass distribution can be adjusted by adjusting the thickness of the part corresponding to the inner frame and the part corresponding to the frame. In the intermediate grid, for example, the mass distribution can be adjusted by adjusting the ratio of the part of the rolled plate removed by punching to the part remaining. If necessary, both of these methods may be combined.

[0043] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, with each main component being described. However, the present invention is not limited to the following embodiment.

[0044] 1A and 1B are plan views showing the appearance of current collectors 100A and 100B according to one embodiment of the present invention and another embodiment, respectively. Both current collectors 100A and 100B have a frame 110 and a mesh-like inner frame 120 inside the frame 110. The frame 110 has an ear 130, an upper element 111 that is continuous with the ear 130, a lower element 112 that faces the upper element 111, and a pair of side elements 113 and 114 that connect the upper element 111 and the lower element 112. The dashed lines indicate the boundaries that divide the inner frame into three equal parts: an upper region, a middle region, and a lower region. The current collector 100A in FIG. 1A has a lower protrusion (also called a foot) 132 that is continuous with the lower element 112. In the current collector 100B in FIG. 1B, the horizontal bones extend in a diagonal direction relative to the upper element or the lower element. LH indicates the inside length per grid of the vertical bones, and LW indicates the inside length per grid of the horizontal bones.

[0045] The current collectors 100A and 100B are, for example, punched lattices of an elongated sheet of lead or a lead alloy, and the elongation direction is the direction indicated by the arrow MD in FIG. 1. Cross section C of the vertical bone 120A is a cross section taken along line IIa-IIa in FIG. 1, and cross section G of the horizontal bone 120B is a cross section taken along line IIb-IIb. The metal structure of the elongated sheet is likely to form a layered or fibrous structure extending in the elongation direction. Thus, a striped pattern is formed on cross section C. On the other hand, a pattern due to cutting of the layered or fibrous structure may be formed on cross section G.

[0046] FIG. 2A is an example of a photograph of a cross section C of a vertical bone 120A, the cross section has an octagonal shape, and a striped pattern of a fibrous metal structure can be seen. FIG. 2B is a conceptual diagram of an example of an octagonal cross section C imitating FIG. 2A. Meanwhile, FIG. 3 is an example of a photograph of a cross section G of a horizontal bone 120B, the cross section shows a pattern due to a cross section perpendicular to the fiber length of the fibrous metal structure. In FIG. 2B, most of the left and right sides of the octagonal cross section C are the second part 220, and the remaining peripheral area is the first part 210. In the first part 210, the stripes of the fibrous metal structure (tangent line S2) have an angle θ1 of less than 45° with the contour (line S1) of the cross section C. Meanwhile, in the second part 220, the stripes of the fibrous metal structure cannot be seen, or the stripes (tangent line S2) have an angle θ2 of more than 45° with the contour (line S1) of the cross section C. In FIG. 2A, there is a region in the outermost layer of second portion 220 where a striped pattern of fibrous texture with a thickness of less than about 55 μm is observed, but this thin portion does not constitute first portion 210.

[0047] Figure 4 is a conceptual diagram of cross section C showing the progression of corrosion of the inner bone. The part where a shallow corrosion layer is formed is the first part, where the fibrous tissue extends along the contour of cross section C, and the corrosion layer is unlikely to form deep even if corrosion progresses. Therefore, peeling tends to occur easily near the interface between the current collector and the electrode material. It is therefore thought that the stress that tries to deform the current collector is easily alleviated. On the other hand, the part where a deep wedge-shaped corrosion layer is formed is the second part. When a deep corrosion layer is formed, the current collector is likely to deform unevenly, the current collector is stretched, and the electrode material is likely to fall off.

[0048] (Positive plate) The positive electrode plate for a lead-acid battery includes the above-mentioned current collector and a positive electrode material held by the current collector (positive electrode current collector). A positive electrode plate called a paste-type positive electrode plate is used. The positive electrode material is the positive electrode plate excluding the positive electrode current collector. The positive electrode plate may have a member such as a mat or pasting paper attached thereto. Such a member (attaching member) is used integrally with the positive electrode plate, and is therefore included in the positive electrode plate. In addition, when the positive electrode plate includes such a member, the positive electrode material is the one excluding the positive electrode collector and the attaching member. However, when an attaching member such as a mat is attached to the separator, the thickness of the attaching member is included in the thickness of the separator.

[0049] As described above, the positive electrode current collector is preferably a punched current collector. As described above, the current collector has a frame and an inner frame inside the frame. As the current collector, a lattice-shaped current collector (positive electrode grid) is preferable. In the positive electrode grid, the inner frame portion is lattice-shaped (including mesh-shaped). By using the positive electrode grid, it becomes easier to support the positive electrode material. The frame is preferably rectangular. Note that the rectangle does not have to be a strict rectangle, and the vertices may be somewhat rounded or each side may be somewhat curved.

[0050] The positive electrode current collector can be formed by pressing a lead or lead alloy sheet. The sheet is preferably a stretched sheet (also called a rolled plate) that has been subjected to a stretching process. The stretched sheet may be a uniaxially stretched sheet or a biaxially stretched sheet.

[0051] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy, or Pb-Sn alloy is preferable. In addition, lead having a purity of three nines or more (purity of 99.9 mass% or more) may be used for the positive electrode current collector. The positive electrode current collector may have a surface layer. It may have a lead alloy layer (surface layer) with a different composition, and the alloy layer may be multiple. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part or only on the frame part of the positive electrode current collector (only on the lug part, only on the frame part other than the lug, etc.).

[0052] The positive electrode material contains a positive electrode active material (lead dioxide or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The positive electrode material may contain an additive, if necessary.

[0053] An unformed paste-type positive plate is obtained by filling a positive current collector with a positive electrode paste, aging, and drying. The positive electrode paste is prepared by kneading lead powder, additives, water, and sulfuric acid. The unformed positive plate is then formed to obtain a positive plate. The formation can be performed by charging the plate group in a state where the plate group including the unformed positive plate is immersed in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery. However, the formation may be performed before assembling the lead-acid battery or the plate group.

[0054] (Negative plate) The negative plate of a lead-acid battery is composed of a current collector and a negative electrode material. The negative electrode material is the negative plate excluding the negative current collector. Note that a member such as a mat or pasting paper may be attached to the negative plate. Such members (attaching members) are used integrally with the negative plate, and therefore are considered to be included in the negative plate. Also, when the negative plate includes such members, the negative electrode material is the negative plate excluding the negative current collector and the attaching member.

[0055] The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a sheet of lead or a lead alloy. Examples of processing methods include expanding and punching. It is preferable to use a lattice-shaped current collector (negative electrode lattice) as the negative electrode current collector, since it is easy to support the negative electrode material. The negative electrode current collector may be a current collector as described for the positive electrode current collector.

[0056] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the lug of the negative electrode current collector. The surface layer of the lug may contain Sn or an Sn alloy.

[0057] The negative electrode material contains as an essential component a negative electrode active material (lead or lead sulfate) that develops capacity through an oxidation-reduction reaction, and may contain additives (organic shrinkage inhibitors, carbonaceous materials, barium sulfate, etc.) The negative electrode active material in a charged state is sponge-like lead, but unformed negative plates are usually made using lead powder.

[0058] The organic shrink-proofing agent may be at least one of lignins and synthetic organic shrink-proofing agents. Examples of lignins include lignin and lignin derivatives. Examples of lignin derivatives include lignin sulfonic acid or its salts (alkali metal salts (sodium salts, etc.)). The synthetic organic shrink-proofing agent is an organic polymer containing elemental sulfur, and generally contains multiple aromatic rings in the molecule and also contains elemental sulfur as a sulfur-containing group. Among the sulfur-containing groups, a sulfonic acid group or a sulfonyl group, which are stable, is preferred. The sulfonic acid group may exist in an acid form or in a salt form such as a Na salt.

[0059] Specific examples of organic shrink-proofing agents include condensates of a compound having a sulfur-containing group and an aromatic ring with an aldehyde compound (aldehyde or its condensate, such as formaldehyde). Examples of aromatic rings include benzene rings and naphthalene rings. When a compound having an aromatic ring has a plurality of aromatic rings, the plurality of aromatic rings may be linked by direct bonds or linking groups (such as alkylene groups, sulfone groups, etc.). Examples of such structures include biphenyl, bisphenylalkane, and bisphenylsulfone. Examples of compounds having an aromatic ring include compounds having the above aromatic ring and a hydroxy group and / or an amino group. The hydroxy group or amino group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a hydroxy group or amino group. Examples of compounds having an aromatic ring include bisphenol compounds, hydroxybiphenyl compounds, hydroxynaphthalene compounds, and phenol compounds. The compound having an aromatic ring may further have a substituent. The organic shrinkage inhibitor may contain one or more of the residues of these compounds.Preferred bisphenol compounds include bisphenol A, bisphenol S, and bisphenol F.

[0060] The sulfur-containing group may be directly bonded to an aromatic ring contained in the compound, or may be bonded to the aromatic ring as, for example, an alkyl chain bearing the sulfur-containing group.

[0061] In addition, for example, a condensation product of the above-mentioned compound having an aromatic ring with a monocyclic aromatic compound (such as aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, phenolsulfonic acid or a substituted product thereof) with an aldehyde compound may be used as the organic shrink inhibitor.

[0062] The content of the organic shrinkage inhibitor contained in the negative electrode material is, for example, 0.01% by mass or more, and may be 0.02% by mass or more or 0.05% by mass or more. On the other hand, the content of the organic shrinkage inhibitor may be, for example, 1.0% by mass or less, 0.8% by mass or less or 0.5% by mass or less. These lower and upper limits can be combined arbitrarily. Here, the content of the organic shrinkage inhibitor contained in the negative electrode material is the content in the negative electrode material extracted from a fully charged lead-acid battery prepared by chemical synthesis using a method described below.

[0063] Carbonaceous materials contained in the negative electrode material may include carbon black, graphite, hard carbon, soft carbon, etc. Examples of carbon black include acetylene black, furnace black, and lamp black. Furnace black also includes Ketjen Black (trade name). Graphite may be any carbon material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite.

[0064] The content of the carbonaceous material in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.2% by mass or more. The content of the carbonaceous material is, for example, 4.0% by mass or less, and may be 3% by mass or less, or 2% by mass or less. These lower and upper limits can be combined in any manner.

[0065] The content of barium sulfate in the negative electrode material is, for example, 0.5% by mass or more, and may be 1% by mass or more, or 1.3% by mass or more. The content of barium sulfate is, for example, 3.0% by mass or less, and may be 2.5% by mass or less, or 2% by mass or less. These lower and upper limits can be combined in any desired manner.

[0066] The following describes the quantitative determination method of the organic shrinkage inhibitor, carbonaceous material, and barium sulfate contained in the negative electrode material. Prior to the quantitative analysis, the lead-acid battery after chemical conversion is fully charged and then disassembled to obtain the negative electrode plate to be analyzed. The obtained negative electrode plate is washed with water to remove sulfuric acid from the negative electrode plate. The washing with water is performed until a pH test paper is pressed against the washed surface of the negative electrode plate and it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative electrode plate is dried at 60±5°C for about 6 hours under a reduced pressure environment. After drying, if the negative electrode plate contains an attachment material, the attachment material is removed from the negative electrode plate by peeling. Next, the negative electrode material is separated from the negative electrode plate to obtain a sample (hereinafter referred to as sample A). Sample A is crushed as necessary.

[0067] Quantitative Analysis of Organic Shrink Resistant The ground sample A is immersed in a 1 mol / L NaOH aqueous solution to extract the organic shrink-preventing agent. Insoluble components are removed by filtration from the NaOH aqueous solution containing the extracted organic shrink-preventing agent. The obtained filtrate (hereinafter also referred to as filtrate B) is desalted, concentrated, and dried to obtain a powder of the organic shrink-preventing agent (hereinafter also referred to as sample C). Desalting is performed using a desalting column, by passing filtrate B through an ion exchange membrane, or by placing filtrate B in a dialysis tube and immersing it in distilled water.

[0068] The organic shrinkage inhibitor is identified by combining information obtained from the infrared spectrum of sample C, the ultraviolet-visible absorption spectrum of a solution obtained by dissolving sample C in distilled water or the like, the NMR spectrum of a solution obtained by dissolving sample C in a solvent such as heavy water, or information obtained from pyrolysis GC-MS, which can obtain information on the individual compounds that make up the substance.

[0069] The ultraviolet-visible absorption spectrum of the filtrate B is measured. The content of the organic shrink inhibitor in the negative electrode material is quantified using the spectral intensity and a previously prepared calibration curve. If the structural formula of the organic shrink inhibitor to be analyzed cannot be precisely identified and a calibration curve of the same organic shrink inhibitor cannot be used, a calibration curve is prepared using an available organic shrink inhibitor that shows a similar ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, NMR spectrum, etc. to the organic shrink inhibitor to be analyzed.

[0070] Quantitative Analysis of Carbonaceous Materials and Barium Sulfate 50 mL of 20% by mass nitric acid was added to 10 g of the crushed sample A, and the mixture was heated for about 20 minutes to dissolve the lead components as lead nitrate. Next, the solution containing lead nitrate was filtered to separate the solids such as carbonaceous materials and barium sulfate.

[0071] The obtained solid content is dispersed in water to obtain a dispersion, and then a sieve is used to remove components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) from the dispersion. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The obtained sample is a mixed sample of the carbonaceous material and barium sulfate (hereinafter also referred to as Sample D). The mass of the membrane filter is subtracted from the total mass of Sample D and the membrane filter after drying to obtain the mass of Sample D (M m ) is measured. After that, the dried sample D is placed in a crucible together with the membrane filter and incinerated at 700°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass of barium sulfate (M B ) is calculated. Mass M m From mass M B The mass of the carbonaceous material is calculated by subtracting the above.

[0072] The negative plate can be formed by filling a negative current collector with a negative paste, aging and drying the negative current collector to produce an unformed negative plate, and then forming the unformed negative plate. The negative paste is produced by adding water and sulfuric acid to lead powder and various additives, and kneading the mixture. In the aging process, the unformed negative plate is preferably aged at room temperature or at a higher temperature and high humidity.

[0073] The formation can be carried out by immersing the plate assembly including the unformed negative plate in an electrolyte containing sulfuric acid in a cell of the lead-acid battery and charging the plate assembly. However, the formation may be carried out before assembling the lead-acid battery or the plate assembly. The formation produces spongy lead.

[0074] (Separator) A separator is usually placed between the negative and positive electrode plates. The separator may be made of a nonwoven fabric, a microporous membrane, or the like. The thickness of the separator between the negative and positive electrode plates may be selected according to the distance between the electrodes. The number of separators may be selected according to the number of gaps between the electrodes.

[0075] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc.) can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers, such as acid-resistant inorganic powder and polymers as binders.

[0076] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent (such as at least one of a polymer powder and an oil) into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably made mainly of a polymer component. The polymer component is preferably polyolefin (such as polyethylene or polypropylene).

[0077] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.

[0078] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since a lug is formed on the top of each of the positive and negative plates, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface of the separator (that is, a double separator is interposed between adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.

[0079] In this specification, the up-down direction of the electrode plate is defined by assuming that the side on which the lugs are provided is the upper side and the opposite side to the lugs is the lower side. The up-down direction of the electrode plate may be the same as or different from the up-down direction of the lead-acid battery in the vertical direction. In other words, the lead-acid battery may be placed either vertically or horizontally.

[0080] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, which may be gelled as necessary. The electrolyte may contain, as necessary, a cation (e.g., a metal cation (e.g., at least one selected from sodium ions, lithium ions, magnesium ions, and aluminum ions) and an anion (e.g., an anion other than a sulfate anion (e.g., a phosphate ion)).

[0081] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.35 or less, and may be 1.32 or less. These lower and upper limits can be combined in any desired manner.

[0082] A lead-acid battery including a positive electrode plate including the above current collector can be manufactured by a manufacturing method including, for example, a step of preparing the above current collector, and a step of obtaining a positive electrode plate including the current collector and a positive electrode material. In the step of preparing the current collector, the current collector is prepared by the above-mentioned method of manufacturing a current collector. More specifically, the current collector is prepared by, for example, a manufacturing method including the above-mentioned steps (i) to (iv). In the step of obtaining the positive electrode plate, the positive electrode plate can be manufactured by the procedure described in the section on the positive electrode plate.

[0083] Furthermore, the lead-acid battery can be obtained by a manufacturing method including a step of assembling the lead-acid battery by housing the positive plate, negative plate, and electrolyte in a battery case. In the assembly step of the lead-acid battery, the separator is usually disposed between the positive plate and the negative plate. The assembly step of the lead-acid battery may include a step of chemically forming at least one of the positive plate and the negative plate, if necessary, after the step of housing the positive plate, negative plate, and electrolyte in the battery case. The negative plate, electrolyte, and separator are each prepared before being housed in the battery case.

[0084] FIG. 5 shows an external appearance of an example of a lead-acid battery according to an embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0085] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0086] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.

[0087] The lid 15 of the lead-acid battery has a single structure (single lid), but is not limited to the illustrated example. The lid 15 may have a double structure including, for example, an inner lid and an outer lid (or a top lid). The lid having a double structure may have a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.

[0088] 5 shows an example of a flooded battery (vented battery), but the lead acid battery may be a valve regulated battery (VRLA type). In a flooded battery, the effect of inhibiting the softening and falling off of the positive electrode material is more likely to be significant than in a valve regulated battery, so the above-mentioned embodiment of the present invention is particularly suitable for a flooded battery.

[0089] Next, the performance evaluation of the lead-acid battery will be described. [Evaluation of test batteries] (A) First single plate overcharge test Using a specified test battery, test it in a water tank at 75°C ± 2°C with a constant current of 1.7A (current density: 0.0054A / cm 2 ) for 5 days, followed by a 2-day rest period (1 week), and repeating this cycle for 3 weeks. The apparent current collector area used to calculate the current density is twice the product of the external height and width of the frame of the positive electrode current collector.

[0090] After the 3-week overcharge test, the positive electrode current collector removed from the fully charged test battery is evaluated as follows: (a) or (b) The positive electrode current collector used for evaluation is removed from the test battery, washed with water, dried, and the electrode material is removed, in the same manner as for the current collector used to form cross section C.

[0091] (a) Corrosion rate The corrosion rate of the positive electrode current collector is calculated using the following formula. Corrosion rate (%) = {(mass of positive electrode current collector before overcharge test - mass of positive electrode current collector from which the corroded layer was removed by mannite treatment after overcharge test) ÷ (mass of positive electrode current collector before overcharge test)} × 100

[0092] (b) Width and height elongation of the positive electrode current collector The dimensions of the most expanded parts in the first direction (height direction) and second direction (width direction) of the frame of the positive electrode current collector are measured, and compared with the initial dimensions to determine the amount of expansion in width and height.

[0093] (B) Second single plate overcharge test Using a specified test battery, an overcharge test is performed in a water tank at 75°C ± 2°C for 5 days at a constant current (a current (A) that is 0.2 times the value obtained by dividing the value (Ah) listed in the 5-hour rate rated capacity by the number of positive plates per cell), followed by a 2-day rest period (1 week), and this operation is repeated for 4 weeks. For example, in the case of a 12V battery with a 5-hour rate rated capacity of 30Ah composed of 6 positive plates and 7 negative plates, the rated capacity of a single-plate cell (1 positive plate, 2 negative plates) is calculated as 30÷6=5Ah, and the current value in the second single-plate overcharge test is 5×0.2=1A.

[0094] After the 4-week overcharge test, the positive electrode current collector is removed from the fully charged test battery, the dimension of the part that expands most in the second direction (width direction) of the frame is measured, and the amount of width expansion is calculated by comparing it with the initial dimension. The positive electrode current collector used for evaluation is prepared by removing it from the test battery, washing it with water, drying it, and removing the electrode material, in the same manner as the current collector used to form cross section C.

[0095] (C) Repeated 5-hour charge-discharge test Use a specified test battery and carry out the following procedure in a water tank at 25°C ± 2°C. Discharge to 1.75V / cell at a constant current (current (A) 0.2 times the value (Ah) listed on the 5-hour rate rated capacity), then charge to 135% of the discharged amount at a constant current (current (A) 0.2 times the value (Ah) listed on the 5-hour rate rated capacity). Repeat the same cycle five times, and calculate the ratio (initial capacity ratio) (%) of the 5-cycle 5-hR discharge capacity to the initial capacity (5-hR discharge capacity) of 100%.

[0096] (D) Repeated 5-hour charge-discharge test after overcharging (after high-temperature overcharging) (a) Third single plate overcharge test Using a specified test battery, an overcharge test similar to the second single plate overcharge test is carried out for 5 days, followed by a 2-day rest period (1 week), and this cycle is repeated for 2 weeks.

[0097] (b) Repeated 5-hour charge-discharge test Using the test battery after the third single plate overcharge test, repeat the 5 hR charge / discharge test in the same manner as in (C) above, and calculate the ratio (initial capacity ratio) (%) of the 5 hR discharge capacity at the 5th cycle to the initial capacity (5 hR discharge capacity) taken as 100%.

[0098] Hereinafter, the embodiment of the present invention will be described in more detail based on examples and comparative examples, but the present invention is not limited to the following examples.

[0099] Lead-acid batteries A11 to A13, B11 to B13, and B21 to B26 (1) Preparation of lead-acid battery (a) Preparation of current collector A rolled sheet of Pb-Ca-Sn alloy is punched, and the inner frame is pressed to obtain current collectors a11 to a13, b11 to b13, and b21 to b26 shown in Table 1. The ratio R1 is adjusted by adjusting the press speed and pressure. The ratio W1 / W2 is adjusted by adjusting the ratio of the part removed by punching and the part remaining when punching the rolled sheet. For current collector a12, the thickness of the inner frame is 0.95 mm, the width of the frame is 1.0 mm, and the WLH / WLW is 1.37. The WLH / WLW of current collectors a11 and a13 is 1.3 or more.

[0100] (b) Preparation of the positive electrode plate A positive electrode paste containing lead powder is prepared, the positive electrode paste is filled into each current collector, and the positive electrode paste is aged and dried to prepare an unformed positive electrode plate. The density of the positive electrode material after formation is 3.6 g / cm 3 Adjust so that:

[0101] (c) Preparation of the negative electrode plate A negative electrode paste is prepared by mixing lead powder, water, dilute sulfuric acid, barium sulfate, carbon black, and an organic shrinkage inhibitor. The negative electrode paste is filled into the same current collector as that used for the positive electrode plate, and the negative electrode paste is aged and dried to obtain an unformed negative electrode plate.

[0102] (d) Preparation of test battery X A lead-acid battery (test battery X: rated voltage 2V, rated 5-hour capacity 6Ah) is assembled using an unformed positive plate containing a positive current collector and positive electrode material. Test battery X is composed of one unformed positive plate sandwiched between two unformed negative plates, and is subjected to formation in an electrolyte. The negative plates are housed in a pouch-shaped separator. An aqueous sulfuric acid solution is used as the electrolyte. After formation, the specific gravity of the electrolyte at 20°C is adjusted to 1.28 in the fully charged test battery.

[0103] (2) Evaluation Using the test battery X, a 5-hour charge-discharge test after high-temperature overcharging is carried out according to the procedure described above. The results are shown in Table 1 and FIG.

[0104] [Table 1]

[0105] As shown in Table 1 and FIG. 6, by setting the ratio W1 / W2 in the range of 0.2 to 0.42, a higher 5hR discharge capacity tends to be obtained even after high-temperature overcharge, compared to when W1 / W2 is outside this range. However, when the ratio R1 of the first portion is less than 50%, even if the ratio W1 / W2 is controlled to be 0.2 to 0.42, the 5hR discharge capacity after high-temperature overcharge is low at a maximum of about 60%. On the other hand, when the ratio W1 / W2 is 0.2 to 0.42 and the ratio R1 is set to 50% or more, a high 5hR discharge capacity of 80% or more can be secured after high-temperature overcharge. This is considered to be due to the fact that by setting the ratio R1 to 50% or more while controlling the ratio W1 / W2 in the range of 0.2 to 0.42, the deformation due to the stress of the corrosion layer itself is reduced, the uneven distribution of the corrosion layer is suppressed, and the falling off of the electrode material is suppressed.

[0106] Lead-acid batteries A31 to A33 and B31 (1) Preparation of lead-acid battery The current collectors a31 to a33 and b31 shown in Table 2 are prepared. The ratio R1 and the ratio W1 / W2 are adjusted in the same manner as in the case of the lead-acid battery A11. The obtained current collectors are used without supporting a positive electrode material to assemble a lead-acid battery (test battery Y). An aqueous sulfuric acid solution with a specific gravity of 1.28 at 20°C is used as the electrolyte. Except for these, the test battery Y is assembled in the same manner as in the case of the lead-acid battery A11. The test battery Y is composed of one positive electrode current collector, two preformed negative electrode plates sandwiching it, and an electrolyte. The negative electrode plates are housed in a bag-shaped separator.

[0107] (2) Evaluation The first single plate overcharge test was performed using the test battery Y according to the procedure described above. The results are shown in Table 2 and FIG. 7. FIG. 7 shows the relationship between the ratio R1, the corrosion rate, and the deformation amount (width and height expansion of the current collector) for the current collectors a31 to a33 and b31. Note that W1 / W2 for a31 to a33 is within the range of 0.2 to 0.42.

[0108] A first single plate overcharge test is performed using the test battery Y according to the procedure described above. The results are shown in Table 2 and Fig. 7. Fig. 7 shows the relationship between the ratio R1, the corrosion rate, and the deformation amount (width expansion and height expansion of the current collector) for the current collectors a31 to a33 and b31. [Table 2]

[0109] As shown in Table 2 and Fig. 7, although the corrosion rate does not change significantly, when the ratio R1 is 50% or more, the height elongation is suppressed, and when the ratio R1 is 60% or more, both the height elongation and the width elongation are significantly suppressed. From the viewpoint of further enhancing the effect of suppressing the width elongation, the ratio R1 may be set to 75% or more or 80% or more.

[0110] 《Lead acid batteries A41~A47》 (1) Preparation of lead-acid battery The current collectors a41 to a47 shown in Table 3 are prepared. The ratio R1 and the ratio W1 / W2 are adjusted in the same manner as in the case of the lead-acid battery A11. The obtained current collectors are used as positive and negative current collectors to prepare unformed positive and negative plates in the same manner as in the case of the lead-acid battery A11. The obtained unformed positive and negative plates are used to assemble a lead-acid battery (test battery Z). The unformed negative plate is housed in a pouch-shaped separator, and eight unformed negative plates and eight unformed positive plates form a plate group. The plate group is housed in a polypropylene battery container together with an electrolyte, and an electrolyte is applied in the battery container to prepare a test battery Z (12 V, rated 5-hour rate capacity 48 Ah). An aqueous sulfuric acid solution is used as the electrolyte. After the electrolyte is formed, the specific gravity of the electrolyte at 20°C is adjusted to 1.28 in the test battery in a fully charged state.

[0111] (2) Evaluation Using the test battery Z, a 5-hR charge-discharge test was repeatedly performed according to the procedure described above. The results are shown in Table 3 and FIG. 8. FIG. 8 shows the relationship between the ratio R1 and the 5-hR discharge capacity (relative to the initial value) (%) when the current collectors a41 to a47 were used. Note that W1 / W2 for a41 to a47 was about 0.3 in all cases.

[0112] [Table 3]

[0113] As shown in Table 3 and Figure 8, when the ratio R1 is 50% or more, a relatively high 5hR discharge capacity is obtained. When the ratio R1 exceeds 95%, the 5hR discharge capacity tends to decrease. Therefore, from the viewpoint of easily securing a higher 5hR discharge capacity, it can be understood that it is preferable to control the ratio R1 to 95% or less.

[0114] Lead-acid batteries A51 to A54 and B51 to B54 (1) Preparation of lead-acid battery Current collectors a51 to a54 and b51 to b54 shown in Table 4 are prepared. The ratio R1 and the ratio W1 / W2 are adjusted in the same manner as in the lead-acid battery A11. The ratio WLH / WLW is adjusted by adjusting the press speed and press pressure. Using the obtained current collectors as the positive and negative electrode current collectors, lead-acid batteries A51 to A54 and B51 to B54 (test battery X) are prepared in the same manner as in the lead-acid battery A11.

[0115] (2) Evaluation A second single plate overcharge test was performed using the test battery X according to the procedure described above. The results are shown in Table 4 and FIG. 9. FIG. 9 shows the relationship between WLH / WLW and width elongation when current collectors a51 to a54 and b51 to b54 were used. W1 / W2 for a51 to a54 was in the range of 0.2 to 0.42.

[0116] [Table 4]

[0117] As shown in Table 4 and FIG. 9, when the ratio R1 is 60%, the width elongation is suppressed, and in this case, the effect of suppressing the width elongation becomes greater as the WLH / WLW ratio increases (especially when the WLH / WLW ratio is 0.8 or more). [Industrial Applicability]

[0118] The current collector for a lead-acid battery according to the present invention is applicable to valve-regulated and flooded lead-acid batteries. A lead-acid battery having an electrode plate including the current collector can be suitably used as a starting power source for vehicles (such as automobiles and motorcycles) and a power source for industrial power storage devices (such as electric vehicles (such as forklifts)). Note that these uses are merely examples and are not limited to these uses. [Explanation of symbols]

[0119] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug 100A, 100B: Current collector 110: Frame 111: Upper element 112: Lower element 113, 114: Side elements 120: Inner bone 120A, B1: Vertical bone 120B: Lateral bone 130: Ear 132: Lower protrusion (foot) 210: First part of longitudinal bone 220: Second part of the longitudinal bone

Claims

1. A current collector for a lead-acid battery, A frame and an inner frame on the inside of the frame, The frame includes an ear, an upper element continuous with the ear, a lower element facing the upper element, and a pair of side elements connecting the upper element and the lower element, The inner rib includes a vertical rib extending in a first direction from the upper element to the lower element, and a horizontal rib extending in a second direction from one of the side elements to the other of the side elements, In a cross section of the longitudinal bone perpendicular to the first direction, a striped pattern of a fibrous structure of metal is observed; The outer peripheral region of the cross section is composed of a first portion in which the fibrous structure extends along the contour of the cross section, and a second portion other than the first portion, a ratio R1 of the length of the contour corresponding to the first portion to the total length of the contour of the cross section is 50% or more; A current collector for a lead-acid battery, wherein a ratio of a mass W1 of the frame to a mass W2 of the inner frame: W1 / W2 satisfies 0.2≦W1 / W2≦0.

42.

2. The lead-acid battery according to claim 1 , wherein the ratio R1 is 60% or more.

3. 3. The current collector for a lead-acid battery according to claim 1, wherein the ratio R1 is less than 100%.

4. A collector for a lead-acid battery as described in any one of claims 1 to 3, wherein the cross section is octagonal.

5. The current collector is a punched current collector made of an expanded sheet of lead or a lead alloy, The lead acid battery collector according to any one of claims 1 to 4, wherein a total length WLH of the vertical ribs and a total length WLW of the horizontal ribs satisfy WLH / WLW≧0.

8.

6. A collector for a lead-acid battery as described in claim 5, wherein the total length WLH of the inner dimensions of the vertical bones and the total length WLW of the inner dimensions of the horizontal bones satisfy WLH / WLW≦1.

96.

7. A positive electrode plate for a lead-acid battery, comprising a current collector according to any one of claims 1 to 6, and a positive electrode material held on the current collector.

8. A lead-acid battery comprising a positive electrode plate as described in claim 7, a negative electrode plate, and an electrolyte.

Citation Information

Patent Citations

  • Namarichikudenchonamarikoshiban

    JP1976060936A

  • Grating for lead-acid battery

    JP1993054893A

  • Electrode plate for lead-acid battery and lead-acid battery using the electrode plate

    JP1994267544A

  • Positive electrode lattice substrate, pole plate using positive electrode lattice substrate, and lead battery using the pole plate

    JP2012174561A

  • Positive electrode plate for lead-acid battery, lead-acid battery and method of manufacturing positive electrode plate for lead-acid battery

    JP2017139215A